Experimental study of geysers through a vent pipe connected to flowing sewers - Huang, Biao (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
Geysers of air-water mixtures in urban drainage systems is receiving considerable attention due to public safety concerns. However, the geyser formation process and its relation with air release from pressurized pipes are still relatively little known. A large-scale physical model, that consisted of a main tunnel with a diameter of 270 mm and a length of 25 m connecting two reservoirs and a vertical vent pipe, was established to investigate geyser evolution and pressure transients. Experimental results including dynamic pressure data and high speed videos were analysed in order to characterize geysering flow through the vent pipe. Pressure transients were observed during geysering events. Their amplitudes were found to be about three times the driving pressure head and their periods were close to the classic surge tank predictions. The influence of flow rate and vent pipe size were examined: geyser heights and pressure peaks decreased for small flow rate and large diameter vent pipe. It is suggested that geyser heights are related with the pressure head and the density of the air-water mixture